Resistive Gas Sensors Based on Porous Sp-Containing Films Obtained by Dehydrohalogenation of PVDC and PVDC-PVC Copolymer - Oleg A. Streletskiy; Ilya A. Zavidovskiy; Islam F. Nuriahmetov; Olesya Y. Nishchak; Alexander V. Pavlikov; Natalya F. Savchenko (C, 2023)
Resistive sensing responses of the thin films obtained by dehydrohalogenation of polyvinylidene chloride (PVDC) and polyvinylidene chloride–polyvinyl chloride (PVDC-PVC) copolymer were investigated. The structure of the samples was studied by transmission electron microscopy, Fourier-transform infrared spectroscopy and Raman spectroscopy. The analyses demonstrate the formation of a porous structure based on polyyne–polyene chains. The formation of a foam-like oxidized sp-rich structure was observed for the samples obtained via the chemical treatment of the PVDC. However, a loose film with a developed structure and a lower fraction of sp-hybridized carbon was observed for KOH-treated PVDC-PVC. The resistive sensing responses of both of the dehydrohalogenated structures were measured for various concentrations of acetone, acetic acid, ammonia hydroxide, methanol, ethanol, benzene and water. The interplay between the efficiency of the dehydrohalogenation of the films, their structure and sensing selectivity is discussed.